Are carbohydrate drinks more effective than preoperative fasting: A systematic review of randomised controlled trials. Issue 17 (10th June 2019) - Noba, Lyrics; Wakefield, Ann
Abstract: Aims and objectives: To evaluate current evidence to determine whether oral preoperative carbohydrate drinks shorten hospital stays, reduce insulin resistance and/or improve postoperative discomfort for patients undergoing abdominal or cardiac surgery. Background: Criticisms of standard preoperative fasting have forced practitioners to explore new ways of preparing patients for theatre. Consequently, the use of preoperative carbohydrate drinks prior to elective surgery has gained momentum. Current evidence regarding the efficacy of this treatment has been inconsistent and contradictory which prompted a review of the current literature. Design: A systematic review of randomised clinical trials (RCTs). Methods: In accordance with Prisma guidelines, the review incorporated a systematic, comprehensive search of English‐language‐only texts published between 2001–2018. The search focused on five databases (MEDLINE, EMBASE, CINAHL, British Nursing Index and ASSIA). Reference lists of relevant systematic reviews and studies located were also hand‐searched for eligibility and further references. All RCTs investigating the effect of preoperative carbohydrate drinks on adult patients undergoing cardiac or abdominal surgery were included. The review excluded RCTs conducted on patients with type 1 or 2 diabetes mellitus and patients under the age of 18. Result: The review included 22 RCTs with a total sample of 2, 065 patients across thirteen countries. Nine different types of surgery were identified. No significant reductions in hospital stay were noted in 8 of the ten trials. Preoperative carbohydrate drinks significantly reduced insulin resistance and improved postoperative discomfort especially in patients undergoing laparoscopic cholecystectomy. No definite conclusion regarding the impact of preoperative carbohydrate drinks on gastric volume and gastric pH was noted. Similarly, no adverse events such as pulmonary aspiration were reported. Conclusion: Preoperative carbohydrate drinks were found to be safe and can be administered up to 2 hr before surgery. Such drinks were also found to reduce insulin resistance and improve postoperative discomfort especially in patients undergoing laparoscopic cholecystectomy. However, there is insufficient evidence to definitively conclude what impact they have on length of hospital stay. Relevance to clinical practice: Patients undergoing surgery are often required to fast from midnight, while in some extreme cases patients are fasted for up to 24 hr prior to surgery. The main purpose of asking patients to undergo this prolonged fasting is to reduce the risk of aspiration. However, there is a general consensus that this traditional practice is out of date, and it is often associated with postoperative complications. On the other hand, current evidence suggests oral intake of fluids up to 90–180 min prior to surgery is safe and consumption of a preoperative carbohydrate drinks does not delay gastric emptying or affect gastric acidity.